Therapeutic Uses of Stem Cells in Endocrinology- Review Article - Ensieh NASLI ESFAHANI; Ardeshir GHAVAMZADEH; Bagher LARIJANI (Tehran University of Medical Sciences, 2015)
Background: Because of the ability of proliferation, regeneration, conversion to differentiated cells and tissue producing, stem cell therapy has important clinical implications for treatment of different diseases. In this chapter we discuss different kinds of stem cells that have been used in treatment of neurologic diseases, gastrointestinal diseases, heart diseases, bone disease, kidney disease, chronic wounds, graft versus heart disease, sepsis and respiratory diseases. Then we will discuss stem cell therapy in treatment of diabetes which is one of the most important diseases of Endocrinology and after that we will provide a brief summary of ethical challenges of stem cell transplantation.   Keywords: Stem-cell therapy, Endocrinology, Diabetes